Analisis Motivasi Kerja Pegawai Bagian Umum Sekretariat Daerah Kabupaten Kuantan Singingi - alsar andri; Askarmin Harun (Kemudi, 2018)
The General Affairs Staff of the Regional Secretariat of Kuantan Singingi Regency in carrying out their dutie and functions within the last five years, namely 2012 to 2016 where during the five year the realization of theactivities never reached the target so the activity funds that were not implemented were returned to the State treasury. Likewise with the number of activities the experience fluctuations even thought activities should incrase every year. Motivation given by the General Section of the Regional Secretariat of Kuantan Singingi Regency to employes was similar to allowance wherein the last five years the performance allowances and job allowances had not changed only welfare benefit had increased. Judging from the type of research this type of research is a descriptive expendited survey and quantitative and qualitative data analysis. The sample in this study is the Civil Service State (ASN) General Section of the Regional Secretariat of Kuantan Singingi Regency in 2016, amouting to 15 people. The result of the study of the overall response weight of respondents 1158 with the average response of respondent is 3.86 which is on the interval scale 3.41-4.20, this shows that responses of respondent to the analysis of employe motivation at the General Section of the Regional Secretariat of Kuantan Singingi Regency is agree or equal to the motivation needed to carry out their duties.